Ireland's Recession and the Immigrant/Native Earnings Gap - Alan Barrett; Adele Bergin; Elish Kelly; Seamus McGuinness (Institute for the Study of Labor (IZA), 2014)
The economic collapse was more severe in Ireland relative to elsewhere. Many questions have arisen concerning the impacts of the collapse, including the impacts on immigrants and their subsequent reactions. Previous research shows that immigrant employment contracted sharply over the recession, thereby suggesting reduced demand for immigrant labour. In this paper, we ask whether immigrants' earnings also fell, relative to natives. Although the raw data shows a widening of the immigrant/native pay gap, when we control for relevant characteristics the adjusted wage gap narrows. A decomposition analysis shows that most of the change in the raw wage gap is generated by the changing composition of the immigrants who were employed.
Keywords: J61; 330; recession; immigrant earnings; Ireland